Voltage Profile Improvement through Load Shedding Action Using Linear Programming-based Optimal Power Flow - Hakim, Lukmanul; Nafisah, Annisa Zauhar; Gusmedi, Heri; Khairudin, Khairudin (International Series on Interdisciplinary Science and Technology, 2018)
This paper proposes a load shedding scheme to improve voltage profile of a power system. A linear programming approach to optimal power flow is utilized to obtain optimum amount of load to shed in order to bring power system to an acceptable operating region. In this work, ±5% voltage variation is considered to be acceptable and hence, an immediate control action should be taken if power system is operated beyond this limit. The proposed method was tested on the IEEE 57-bus test system. Results showed that the proposed approach was able to provide a minimum amount of load shedding action to improve voltage profile of the studied power system.